Recent Developments in Nonlocal Theory - Kuusi, Tuomo (De Gruyter, 2018)
This edited volume aims at giving an overview of recent advances in the theory and applications of partial differential equations and energy functionals related to the fractional Laplacian operator as well as to more general integro-differential operators with singular kernel of fractional differentiability.